Effect of iodine incorporation to the electrical properties of amorphous carbon thin films: article / Mohd Fadhil Yusuff - Yusuff, Mohd Fadhil (2013)
Amorphous carbon (a-C) thin films were deposited on glass and silicon substrates by thermal chemical vapor deposition (CVD) technique using camphor oil as the precursor. After deposited the a-C thin films, the iodine (I) was doped on the a-C thin films using the same technique of deposition of a-C thin film. All the samples were grown in fixed conditions except the doping temperature parameter was varied. The effect of doping temperature in the a-C and a-C:I thin films on electrical, structural and optical properties was characterized by using a standard two-probe method using BUKOH KEIKI (CEP-2000) Solar simulator/Spectral sensitivity Measurement, RAMAN spectroscopy and UV-Vis-NIR spectroscopy respectively. The conductivity of a-C:I thin films increased to 7.44 x 10-3 S.cm-1 with the doping temperature up to 450oC and it shows photoresponse is 1.063 at doping temperature 450oC. The UVVis-NIR analysis was used to obtain the optical absorption coefficient and optical band gap. The absorption coefficient at sample 450oC increase from 8763 cm-1 to 39292 cm-1 and the optical band gap decrease from 0.33eV to 0.08eV. The RAMAN scattering analysis was used to prove the amorphous structure of a-C and a-C:I thin films and it revealed at D-peak (1340 cm-1) and G-peak (1590 cm-1).